The Effect of Profitability, Tunneling Incentive, Good Corporate Governance, and Intangible Assets on Transfer Pricing in Companies in the Basic Materials Sector Listed on the Indonesia Stock Exchange in 2021 – 2023 - Beatrice, Michelle; Setyarini, Yulia (Jurnal Indonesia Sosial Sains, 2025)
Transfer pricing is a strategy employed by companies to shift tax burdens, particularly among entities with special relationships. Although legally permissible when conducted in accordance with the arm’s length principle and business norms, this practice is often misused as a means of tax avoidance, potentially reducing state revenue. This study aims to examine the effect of profitability, tunneling incentive, good corporate governance, and intangible assets on transfer pricing in basic materials sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. This research utilizes secondary data obtained from the annual reports of 113 companies, with purposive sampling applied to select 82 companies as the research sample. Data analysis was conducted using multiple linear regression with SPSS version 27. The results reveal that profitability and tunneling incentive have a significant negative effect on transfer pricing, while good corporate governance has a significant positive effect. In contrast, intangible assets show no significant effect on transfer pricing. These findings highlight the importance of strengthening corporate governance and monitoring transfer pricing practices to prevent misuse that could harm state revenue.